Unique biofilm signature, drug susceptibility and decreased virulence in Drosophila through the Pseudomonas aeruginosa two-component system PprAB. - Sophie de Bentzmann (Public Library of Science (PLoS), 2012)
Bacterial biofilm is considered as a particular lifestyle helping cells to survive hostile environments triggered by a variety of signals sensed and integrated through adequate regulatory pathways. Pseudomonas aeruginosa, a Gram-negative bacterium causing severe infections in humans, forms biofilms and is a fantastic example for fine-tuning of the transition between planktonic and community lifestyles through two-component systems (TCS). Here we decipher the regulon of the P. aeruginosa response regulator PprB of the TCS PprAB. We identified genes under the control of this TCS and once this pathway is activated, analyzed and dissected at the molecular level the PprB-dependent phenotypes in various models. The TCS PprAB triggers a hyper-biofilm phenotype with a unique adhesive signature made of BapA adhesin, a Type 1 secretion system (T1SS) substrate, CupE CU fimbriae, Flp Type IVb pili and eDNA without EPS involvement. This unique signature is associated with drug hyper-susceptibility, decreased virulence in acutely infected flies and cytotoxicity toward various cell types linked to decreased Type III secretion (T3SS). Moreover, once the PprB pathway is activated, decreased virulence in orally infected flies associated with enhanced biofilm formation and dissemination defect from the intestinal lumen toward the hemolymph compartment is reported. PprB may thus represent a key bacterial adaptation checkpoint of multicellular and aggregative behavior triggering the production of a unique matrix associated with peculiar antibiotic susceptibility and attenuated virulence, a particular interesting breach for therapeutic intervention to consider in view of possible eradication of P. aeruginosa biofilm-associated infections.